Surface strength analysis of silicon alloys sintered using the combustion synthesized β/O’-SiAlON powders - Tomomi HONDA; Akiko MATSUSHITA (Nihon Kikai Gakkai ronbunshu, 2019)
To improve the fuel efficiency of automobiles, the development of lightweight and high-strength material is required. Silicon, as a raw material for this purpose has attracted attention. So as method using silicon, Si alloys have been developed. Combustion synthesized β/O’-SiAlON powders were sintered by the hot pressing. Combustion synthesis is known as a self-propagating high-temperature synthesis (SHS). It is possible to design various materials with different properties by varying the ratio of Si, Al, O, and N because the composition of Si alloys is similar to that of SiAlON. In the present study, we prepared five types of Si alloys (S1, S2, O25, O75 and O100), which are similar to material design concept of β/O’-SiAlON having heat resistance and oxidation resistance, and used Si3N4 as a comparative material. We investigated the surface strength by performing the scratch test. In scratch tests, the load at which the fracture progresses to large-scale brittle fracture becomes larger in the order of O100, S1, O75, Si3N4, O25 and S2. The crystallite size of O25 is the smallest in Si alloys. Then, the composition of Al in S2 is the largest in Si alloys. Therefore, it found that Si alloy, which has small crystallite and contains more Al, shows high critical fracture load.